Efek Ekstrak Biji Kapas (Gossypium hirsutum) terhadap Kualitas dan Perkembangan Embrio Mencit (Mus musculus) - Zayani, Nofri; Yulita, Ramadani (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2024)
The cottonseed contained gossypol which can reduce fertility by distrupting follicles and oocytes formation process and development. Folliculogenesis disorder can reduce quality and competence of oocytes to be fertilized. It has an impact on the quality and development of the embryo. The objective of this study was to evaluate the cottonseed extract effect on the quality and development of mice embryos. The research used a total experiment with completely randomized design consist of 4 treatments (0; 1.5; 2.1; and 2.7 g/kg BW EBK) and 6 replications. EBK are extracted maceration using ethanol 80%. EBK administration was orally injection for 24 days. Last day of EBK administration, mices were mated. Embryos were collected on the 4 days of pregnancy by flushing the uterine cornua, then development stage and quality of embryos were determined. Embryos were then cultured in vitro for 48 hours in culture medium PBS supplemented by 10% FBS. The result showed that EBK 2.7 g/kg BW dose can reduce embryos quality by finding retarded, degenerated, and unfertilized oocytes. The decreased embryos number and ability to progress to the blastocysts, expanded blastocysts, and hatched blastocysts stage occurred after culture for 48 hours. Retarded (4-8 cells) and degenerated embryos are not development in 24 hours culture. In conclusion, EBK is able reduce quality and development inhibit of mice embryos, so that it can be used as candidates for herbal contraception.